“Factores de riesgo asociados a Hemorragia Postparto en Pacientes atendidas en el Hospital IESS Riobamba, año 2018” - Gustavo Amilcar, Noroña Vargas,Angélica María, Gaibor Verdezoto (2020)
Starting from a point where we consider that pregnancy and childbirth are physiological acts, periodic monitoring and monitoring of vital signs are part of the care. Within the normal course of pregnancy there is the possibility that there is a vital risk including the postpartum stage, this risk can not always be prevented or predicted, so it remains a challenge for the entire health team that is responsible for your care. Due to women who do not attend their prenatal check-ups and the complications that may occur during pregnancy, maternal mortality is high. It is estimated that every day 830 women die worldwide due to complications related to postpartum hemorrhage. It is alarming and draws attention that these deaths occur in low-income countries and most of them could have been avoided